2016
DOI: 10.3389/fphys.2016.00326
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Classical Time-Trial Performance and Technique-Specific Physiological Determinants in Elite Female Cross-Country Skiers

Abstract: The present study investigated the contribution of performance on uphill, flat, and downhill sections to overall performance in an international 10-km classical time-trial in elite female cross-country skiers, as well as the relationships between performance on snow and laboratory-measured physiological variables in the double poling (DP) and diagonal (DIA) techniques. Ten elite female cross-country skiers were continuously measured by a global positioning system device during an international 10-km cross-coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 28 publications
11
82
0
Order By: Relevance
“…Altogether, the stepwise multiple regression analysis demonstrated that time in uphill explained ∼91% of the variation in XC skiing performance. Indeed, uphill terrain as the most performance-differentiating part of the XC skiing performance is supported by previous research in XC skiing (Andersson et al, 2010;Bolger et al, 2015;Sandbakk et al, 2016b;Solli et al, 2018). However, in line with findings from XC skiing (Sandbakk et al, 2016b), performance in all types of terrain are important for achieving an excellent XC skiing performance in biathlon as shown by the significant correlations between all types of terrain and isolated skiing performance in this biathlon sprint race.…”
Section: Skiing Performancesupporting
confidence: 85%
“…Altogether, the stepwise multiple regression analysis demonstrated that time in uphill explained ∼91% of the variation in XC skiing performance. Indeed, uphill terrain as the most performance-differentiating part of the XC skiing performance is supported by previous research in XC skiing (Andersson et al, 2010;Bolger et al, 2015;Sandbakk et al, 2016b;Solli et al, 2018). However, in line with findings from XC skiing (Sandbakk et al, 2016b), performance in all types of terrain are important for achieving an excellent XC skiing performance in biathlon as shown by the significant correlations between all types of terrain and isolated skiing performance in this biathlon sprint race.…”
Section: Skiing Performancesupporting
confidence: 85%
“…From an energy-supply perspective, it is important to be able to effectively use metabolic energy in the force-generating muscles in the upper body. This is supported by correlations between elite skiers’ performance capacity and peak oxygen uptake using the double-poling technique () (Carlsson et al 2012, 2014; Mahood et al 2001; Sandbakk et al 2016). It has been suggested that gross efficiency using double-poling technique (GE) (i.e.…”
Section: Introductionmentioning
confidence: 91%
“…The competition terrain fluctuates between uphill, flat and downhill sections, in which the greatest performance variation is seen in the uphill terrain, [1][2][3][4] and the relative time spent on uphill, flat and downhill sections contribute in that order to overall timetrial performance. 5 Due to the varying terrain in XC skiing, the competitions are interval-based with increased generation of external work rate and metabolic intensity uphill, and reduced effort in the downhill terrain. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16] Currently, these factors have only been examined in a performance setting at high-intensity (HIT), and no previous study has investigated whether the same occurs while training at low-(LIT) and moderate-intensity (MIT) that reflects around 80% of a XC skier's overall training.…”
Section: Introductionmentioning
confidence: 99%
“…5 Due to the varying terrain in XC skiing, the competitions are interval-based with increased generation of external work rate and metabolic intensity uphill, and reduced effort in the downhill terrain. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16] Currently, these factors have only been examined in a performance setting at high-intensity (HIT), and no previous study has investigated whether the same occurs while training at low-(LIT) and moderate-intensity (MIT) that reflects around 80% of a XC skier's overall training. [17][18][19][20][21][22][23][24][25] Heart rate (HR) is commonly normalized to its maximal value (HRmax) to reflect an individual's internal metabolic intensity/effort during training and competition.…”
Section: Introductionmentioning
confidence: 99%